THE CORRELATION BETWEEN TOURISM ACCOMMODATION CAPACITY AND TOURIST INFLOW BY MICRO REGION OF DEVELOPMENT IN ROMANIA - Agatha POPESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aimed to analyze the relationship between the tourism accommodation capacity in terms of the number of units, and the number of tourist flows in terms of arrivals in Romania and by its 8 micro regions in the period 2007-2015. In this purpose, the data provided by the National Institute of Statistics were processed using the indices with fixed and variable basis, comparison method, statistical parameters, Pearson coefficient of correlation, and linear regression function. In Romania, the number of units with accommodation function increased by 65.3 % from 4,694 units in the year 2007 to 6,821 units in the year 2015, and the number of tourists' arrivals increased by 63 % from 6,091.9 thousands in 2007 to 9,930.4 thousands in 2015. While the highest number of accommodation units is in the Central, SE and NE Romania, the highest number of tourists' arrivals was recorded in the Central Romania, Bucharest Ilfov and SE region. Even thou at the national level, the average number of tourists' arrivals per unit for tourists' accommodation was 1,456 arrivals/unit, by 12.18 % higher in 2015 compared to 2007, there is still a gap between the territorial dispersion of the accommodation capacity and the tourists flow. The high correlation coefficient r = 0.909 and the high determination degree 82.76 % at the national level, reflect that tourists flow has a major influence on the tourism accommodation capacity. Using the linear regression functions, there were estimates the units for tourists' accommodation depending on the tourists' arrivals for the period 2016-2020. In conclusion, the development of tourism accommodation capacity must be a priority in order to assure a better correlation with the tourist arrivals in the territory of Romania.